2022
DOI: 10.31925/farmacia.2022.1.24
|View full text |Cite
|
Sign up to set email alerts
|

The Direct Costs Burden of Bevacizumab in South-West Romania

Abstract: As costs for cancer treatment increase with the reimbursement of new treatments and increasing of patients' number, prevention and prior detection efforts become even more cost-effective and potentially cost saving. The global economic burden of cancer is mostly unknown. Even though bevacizumab is one of the most prescribed and used angiogenesis inhibitors, it is among the most expensive drugs. This study aimed to generate statistical analyses of the total amounts reimbursed by the Romanian National Health Ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Using this strategy, we can obtain a wealth of descriptive information on people's attitudes, behaviours, and perceptions [30]. The following benefits of in-depth interview methods [15] are beneficial for this study:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using this strategy, we can obtain a wealth of descriptive information on people's attitudes, behaviours, and perceptions [30]. The following benefits of in-depth interview methods [15] are beneficial for this study:…”
Section: Methodsmentioning
confidence: 99%
“…For patients receiving a haematopoietic cell transplant, an additional point in the peak mucositis score resulted in an additional USD25,000 in hospital expenses [14]. In treating several cancers, surgery, chemotherapy (including immunotherapy or target therapy), and radiotherapy may be employed, and the expenditures involved with all these efforts are substantial [15].…”
Section: Examining the Use Of Fsmps In Cancer Care: Treatment Benefit...mentioning
confidence: 99%
“…This kind of analysis is performed when the health-related quality of life (HRQOL) is considered an important outcome. 24 Some studies addressed and compared the costs [25][26][27][28] or effectiveness [29][30][31][32] of the drugs investigated in this study separately. Some others investigated the cost-effectiveness of various drug combinations used in the treatment of stage IV colorectal cancer (not the drug combinations examined in the present study).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies addressed and compared the costs 25 - 28 or effectiveness 29 - 32 of the drugs investigated in this study separately. Some others investigated the cost-effectiveness of various drug combinations used in the treatment of stage IV colorectal cancer (not the drug combinations examined in the present study).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the conduction pathway of biological signalling molecules has become the focus of colorectal cancer treatment, and commonly used drugs include cetuximab, panitumumab and bevacizumab [5][6][7]. Bevacizumab is a human-mouse chimeric monoclonal antibody, which can effectively bind tissue ligands to vascular endothelial growth factor, thereby inhibiting the proliferation and metastasis of tumour cells and promoting apoptosis [8]. Rubinstein et al [9] used bevacizumab in the treatment of advanced endometrial cancer and found that it could effectively improve the clinical treatment effect.…”
Section: Introductionmentioning
confidence: 99%